Dose constraints for whole breast radiation therapy based on the quality assessment of treatment plans in the randomised Danish breast cancer group (DBCG) HYPO trial. (May 2021) - Thomsen, M.S.; Berg, M.; Zimmermann, S.; Lutz, C.M.; Makocki, S.; Jensen, I.; Hjelstuen, M.H.B.; Pensold, S.; Hasler, M.P.; Jensen, M.-B.; Offersen, B.V.
Highlights: Quality assurance of all treatment plans (1854 patients) in the DBCG HYPO trial is presented. More strict dose constraints for high-dose volumes of the breast in whole breast RT are suggested. Laterality-specific dose constraints for organs at risk (OAR) in whole breast RT are presented. Abstract: Purpose: Quality assessment of the treatment plans in the Danish Breast Cancer Group (DBCG) HYPO trial was carried out based on prospectively reported dosimetric parameters and evidence-based dose constraints for whole breast radiation therapy were derived. Materials and methods: From 2009 to 2014, 1882 patients (pts) were randomised between 50 Gy/25fractions (fr) versus 40 Gy/15fr. Doses to CTVp_breast (V95%, V107% -V110%, Dmax, and in addition for 40 Gy plans V105% -V107% ), ipsilateral lung (V20Gy /V17Gy ), heart (V20Gy /V17Gy, V40Gy /V35Gy ), and left anterior descending coronary artery (LADCA) (Dmax ) and use of respiratory gated technique were prospectively reported to the DBCG database. After end of accrual, these dosimetric parameters from all plans in the trial were compared to the pre-specified treatment constraints. Results: In total, 1854 pts from eight radiation therapy (RT) centres in three countries were treated. No statistically significant differences were found between the results for 40 Gy and 50 Gy plans, except for CTVp_breast hot-spot volume (V107% -V110% ). Of the 40 Gy pts, 90% with CTVp_breast > 600 mL and 95% with CTVp_breast ≤ 600 mL had a CTVp_breast hot-spot volume (V105% -V107% ) <2%. In 95% of the 50 Gy plans, the CTVp_breast absolute hot-spot volume (V107% -V110% ) was <0.5 mL and 1.7 mL for CTVp_breast ≤ 600 mL and > 600 mL, respectively. Compliance was >99% for both heart and lung constraints. Largest deviation from protocol constraints was found for the volume of CTVp_breast covered with 95% of the prescription dose or more (V95% ). The CTV dose coverage (V95% ) was >94.3% in 95% of the right-sided pts, whereas the figures for 95% of the left-sided pts treated with and without respiratory gating were 93.2% and 88.8%, respectively. Conclusion: A high degree of compliance with protocol dose constraints was found for treatment plans in the DBCG HYPO trial. New constraints for dose to organs at risk and high-dose volumes in the breast are suggested for breast-only RT planning.